The Effects of Target, Guardianship, and Lifestyle Characteristics on Stalking Victimization Risk among College Students - Ménard, Kim S. (Victims & offenders, 2025)
Guided by lifestyles/routine activities and target congruence theories and using data from a campus climate survey from a large northeastern university, this study explored the influence of target (e.g., mental health, age, race), guardianship (e.g., relationship status, residency), and lifestyle characteristics (e.g., collegiate activities) on the risk of stalking victimization among 7,621 undergraduates. In addition to running models for the full sample, separate logistic regressions were completed for men (n = 3,544) and women (n = 4,077), and for those who identify as either lesbian, gay, bisexual, trans, or queer (LGBTQ, n = 612) and those who do not (non-LGBTQ, n = 6,923). Results show target vulnerabilities including having lower scores on mental health and being younger increased victimization risk, guardianship factors including being married or living with parents or on campus reduced the risk of victimization, and lifestyle characteristics including participation in collegiate activities increased victimization risk. Consistent with prior research, those who identify as LGBTQ and women had higher odds of victimization than their respective counterparts. However, coefficient tests revealed only three risk factors varied significantly across sex (i.e., age and media activity) and LGBTQ status (i.e., mental health). Implications for research and campus policy are discussed.